Legal Policy Conception of Drug Abuse Prevention in Higher Education (Study on the prevention of drug dangers through courses) - Zulkarnain, Zulkarnain; Alfauza, Zaid (Faculty of Law, Universitas Pekalongan, 2024)
Abstract The concept of preventing drug abuse through universities has never been carried out, until now universities have implemented drug abuse prevention on campus, but the prevention is only active, not yet a structured program. Another problem is that many high school leaders still view a victim of abuse and addicts as a criminal. This study aims to formulate the concept of drug abuse prevention in higher education through courses. This research is an empirical research with a descriptive nature of analysis. The results of this study show that legislation has mandated the prevention of drug abuse in universities. The concept of preventing drug abuse in Indonesia through courses can be done by making the Anti-Drug Investigation Course into a General Course (MKDU) and special courses for certain study programs that are directly related to drug problems such as the Addiction Counseling Course and the Narcotics Crime Course. Prevention of drug abuse through courses in Indonesia has strategic prospects. With the existence of Anti-drug education courses, the campus is directly involved in the prevention of drug abuse. Furthermore, prospects in the context of developing drug courses can be carried out, including the preparation of teaching materials or Anti-Drug Education Books. Furthermore, future research is expected to be able to create a drug-clean campus with clear indicators and measurable standards.